Makna Kearifan Lokal Tradisi Bauma Batahutn Suku Dayak Kanayatn di Kalimantan Barat - Piter, Romanus (Universitas Tanjungpura, 2023)
The Bauma Batahutn tradition is the local wisdom of the Dayak Kanayatn tribe in West Kalimantan. Bauma Batuhutn is an agricultural activity of planting rice traditionally in fields and paddy fields. The Dayak Kanayatn people in this modern era still carry out agricultural activities in this traditional way. The purpose of this research is to explain more comprehensively about the Bauma Batatutn tradition and find the meaning contained in it. The methodology used in this study is an ethnographic study with the thick description theory of Clifford Geertz. The location of this research is Dano Village, Kaca’ Lengkuas Hamlet, Garu Village, Mempawah Hulu District, Landak Regency, West Kalimantan Province. This study uses three data sources namely: (1) the author's direct experience; (2) results of in-depth interviews with farmers and traditional leaders; (3) literature review. This study found that the local wisdom of the Bauma Batahutn tradition of the Dayak Kanayatn tribe contains the meaning of transcendental awareness, ecological awareness, democratic awareness, mutual cooperation and visiting, as well as the collective awareness of an agrarian society which appears in resemblance to the agricultural traditions of other ethnic cultures.